Larval ground plan of Platynectes Régimbart, 1879 reconsidered: description of the larvae of three species with phylogenetic considerations (Coleoptera: Adephaga, Dytiscidae) - Alarie, Yves; Michat, Mariano C.; Short, Andrew E. Z.; Watts, Chris H. S. (Zootaxa, 2024)
In this contribution we describe and illustrate for the first time the larvae of three species of Platynectes Régimbart, 1879 (P. agallithoplotes Gustafson, Short & Miller, 2016, P. bakewelli (Clark, 1863), and P. reticulosus (Clark, 1863)) including detailed morphometric and chaetotaxic analyses of selected body structures in order to discover useful characters for distinguishing Platynectes larvae from those of other known Agabinae (Coleoptera: Dytiscidae). A parsimony analysis based on larval characteristics of 19 Agabinae species in six genera (Agabus Leach, 1817, Agabinus Crotch, 1873, Hydrotrupes Sharp, 1882, Ilybiosoma Crotch, 1873, Platynectes, and Platambus Thomson, 1859) was conducted using the program TNT. The results support Platynectes as a natural group whilst the six species studied split into two well supported clades: P. agallithoplotes + P. decemnotatus (Aubé, 1838) and P. curtulus (Régimbart, 1899) + P. davidorum Hájek, Alarie, Šťastný & Vondráček, 2019 + P. reticulosus + P. bakewelli. Larvae of P. agallithoplotes have proven to be characterized by a large number of unique character states, several of which were never observed until now in the Agabinae. Evidence is provided to the effect that the Neotropical species of Platynectes s. str. evolved as a unique lineage within Platynectes.